Effects of gestational and lactational exposure to ethanol on body and bone growth of rat offspring - Natalia Viana Tamiasso; Fabiana Rocha Araújo; Natália de Melo Ocarino; Amanda Maria Sena Reis; Athelson Stefanon Bittencourt; Rogéria Serakides (ABCS Health Sciences)
Introduction: Ethanol is the most widely consumed drug in the world. When this consumption occurs by pregnant women, the harmful effects extend to the fetus. There are few data available on its effects on infants. Objective: To evaluate the effects of maternal ethanol consumption during pregnancy (prenatal) as well as during pregnancy and lactation (pre- and post-natal). Methods: 12 Wistar rats were divided into ethanol and control groups. Ethanol group received ethanol (4 g/kg/day) via oral gavage from the ninth day of gestation to the 17th day of lactation. The weight and length of the pups were determined at birth and 17 days of age. The length and width of the femur and tibia and the thickness of the epiphysis were measured in the neonates, and the thickness of the articular cartilage, epiphyseal plate, and its zones were measured at 17 days of age. CDC-47 immunoexpression was evaluated and the expressions of aggrecan, collagen type II, and collagen type X were determined by RT-PCR. Results: In neonates, rats in the group with prenatal exposure to ethanol were significantly shorter (body length) than the control group. At 17 days of age, the femur of the group with pre-and postnatal exposure to ethanol showed a significantly lower percentage of proliferating chondrocytes, as evidenced by the different CDC-47 immunoexpression between groups. Conclusion: Prenatal exposure to ethanol in rats reduced body length at birth while pre- and postnatal exposure to ethanol decreased the proliferation of femoral epiphyseal plate chondrocytes.